Analisis Dinamik Tegasan Purba pada Satuan Batuan Paleogen â Neogen di Daerah Pacitan dan Sekitarnya, Provinsi Jawa Timur Ditinjau dari Studi Sesar Minor dan Kekar Tektonik - C. I. Abdullah; N. A. Magetsari; H. S. Purwanto (Institute for Research and Community Services (LPPM) ITB, 2003)
There are four trends of geological structures in the region of Pacitan and its closed surrounding, as the result of the tectonic deformation which occured during the Tertiary up to Quaternary. Those trends of geological structures are classified as fault groups in the direction of NW - SE (N3100E - N3300E), N - S (N3500E - N0100E), NE - SW (N0450E - N0500E), and E - W (N0800E). The result of the paleostress reconstruction based on the minor faults and shear fractures, point to three axis direction of principle stress: First, Early Miocene Stress with the ï³1 direction between 150, N1640E - 090, N1700E. The respective stress caused the formation of fault in the direction of NW - SE and fold structures. Second, Middle Miocene Stress with the ï³1 direction between 160, N1920E